ANALISIS FAKTOR INTERNAL DAN EKSTERNAL PERUSAHAAN TERHADAP HARGA SAHAM SEKTOR CONSUMER GOODS INDUSTRY DI BURSA EFEK INDONESIA (BEI) - Syahril Effendi; Baru Harahap (Pusat P2M Politeknik Negeri Batam, 2020)
This study aims to determine the effect of a given return on equity, earnings per share, Inflation and Interest Rates on Stock Prices on the company's sector of consumer goods industry listed on the Indonesia stock Exchange. The population in this study consisted of 49 companies engaged in the sector of consumer goods industry listed in Bursa efek Indonesia (BEI). Sampling technique in this study using purposive sampling and there are 10 companies that meet the criteria for the selection of the sample. Financial Data in this research was obtained through IDX representative of Kepri. As for the inflation data and the interest rate is obtained from Central bureau of Statistics and Bank Indonesia. The research results of the F test show a significant influence of the mean return on equity, earnings per share, inflation and interest rates simultaneously have a significant influence on stock prices so that the regression model contained in this study deserve to be studied. Partially by t test obtained the result that variable return on equity and earnings per share have a significant effect on stock prices, while variable inflation and interest rates do not significantly influence the stock price